Predictors of syphilis infection among HIV pre-exposure prophylaxis users - Nguyen, Thanh Tran Ai; Vu-Tri, Thanh; Nguyen, Vu Hoang Anh; Nguyen-Thi, My-Tien; Luu-Thi, Huyen-Trang; Ly, Thanh-Thao; Phan, Yen Thi Hoai (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Pre-exposure prophylaxis (PrEP) has revolutionized HIV prevention worldwide. However, research has shown a contradictory trend in which PrEP helps reduce HIV incidence, but increases sexually transmitted infections (STIs), especially in high-risk groups like men who have sex with men and female sex workers. This study aimed to examine the association between sex, age, occupational status, hepatitis B virus (HBV) infection, and hepatitis C virus (HCV) infection with syphilis infection among PrEP users. METHODS The cross-sectional survey was conducted over 1 year, with 864 participants in Thu Duc City Hospital, Vietnam. The chi-square test was utilized for descriptive analysis. Binary logistic regression models estimated the association between sex, age, occupational status, HBV infection, and HCV infection with syphilis infection. Odds ratio (OR) and 95% confidence intervals (CIs) were calculated. RESULTS Of 864 participants, 147 (18.2%) men and 68 (23.7%) employed individuals were tested positive for syphilis. The findings indicated that men (OR = 13.805; 95% CI = 1.886−101.024), employed individuals (OR = 1.838; 95% CI = 1.191−2.834), and HBV infection (OR = 2.076; 95% CI = 1.108−3.891) were significantly associated with an increased risk of syphilis infection. CONCLUSIONS Men, employed individuals, and individuals infected with HBV face a higher risk of syphilis infection among PrEP users.